Please do this step by step I will surely help you
Attachments:
![](https://hi-static.z-dn.net/files/d96/7129f8090619f6b87f314a859a2766de.jpg)
Answers
Answered by
0
Answer: x²y³(2+x)
Step-by-step explanation:
x²y³+3x³y³+3x²y³-2(x³y³+x²y³)
= x²y³+3x³y³+3x²y³-2x³y³-2x²y³
= (x²y³-2x²y³+3x²y³)+(3x³y³-2x³y³)
= 2x²y³+x³y³
=x²y³(2+x)
Similar questions
Biology,
2 months ago
Biology,
2 months ago
Social Sciences,
2 months ago
Hindi,
5 months ago
History,
5 months ago
English,
1 year ago
Environmental Sciences,
1 year ago